Eksplorasi Bentuk Jamak Qillah Dalam Surat Lukman: Analisis Morfologi - Rahmawati, Lesa (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study aims to explore the forms of Plural Qillah in the letter of Luqman through morphological analysis. Plural Qillah is one of the categories of plural estimates in Arabic which indicates a small number, generally between three and ten, with certain morphological patterns such as Af'aal, Af'ul, Af'ilah This study uses a qualitative-descriptive method with an approach to analyzing the text of the Qur'an, especially in the letter of Luqman. The results of the study show that Luqman's letter contains several phrases that follow the qillah plural pattern, including (abhur), (aqlaam), (aswaat), (af’idah), and (arhaam). Morphological analysis shows that the choice of the qillah plural form in Luqman's letter not only functions grammatically, but also provides a stylistic effect and strengthens the message of meaning in the verse. In addition, there is a phenomenon of deviation between the morphological form and the literal meaning of the number in several phrases, which enriches the beauty and rhetorical power of the language of the Qur'an. This study emphasizes the importance of morphological studies in understanding the message and uniqueness of the language structure of the Qur'an.